Estructuración psíquica de adolescentes pandilleros de una fundación de la ciudad de Cartagena - Alcalá Arenas, Milton (Psicología, 2017)
This is a final report entitled psychic structuring teenagersgangs a foundation for the city of Cartagena, it was born because of a problem, which although not new, is at its greatest boom in the city of Cartagena, actually gangsterism, which is increasingly and right now it´s attracting younger teens and also bringing with it self greater damages caused by this. The objective of this research is to understand the psychic structure of a group of teenage gang foundation renovación yesperanza. This was done using two projective tests, which were: test of the human figure and test the of the tree, also an open semi-structured interview. This is not to generalize, but try to understand the way these teens think and as their psychic structure, which is useful for further investigations.